2018
DOI: 10.1177/2277975218769501
|View full text |Cite
|
Sign up to set email alerts
|

Market State and Investment Strategies: Evidence from the Indian Stock Market

Abstract: This study contributes to the growing literature on momentum and overreaction effect by investigating the same within the framework of the Indian stock market. Based on the most adopted methodology that employs monthly data, the empirical results derived confirm the existence of momentum and long-term overreaction effect in the Indian stock market. The overall results from the study are consistent with DeBondt and Thaler (1985) and Jegadeesh and Titman (1993) findings for the US stock market. In addition, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…One of the most important determinants of cash holding is the sales growth rate, since firms with high investment opportunities have a greater degree of uncertainty in achieving future cash flows, in addition to information asymmetry, and therefore may keep more cash holding to ensure the firm's ability to finance future investments when the internal cash flow is low (Kim, Firm size is an important factor in determining the level of cash holding. Some of the literature argued that there is a negative relationship between firm size and cash holding, since small-sized firms are more exposed to irregular risks and borrowing restrictions, and then managers tend to maintain a higher level of cash holding to meet these restrictions and risks (Maheshwari et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most important determinants of cash holding is the sales growth rate, since firms with high investment opportunities have a greater degree of uncertainty in achieving future cash flows, in addition to information asymmetry, and therefore may keep more cash holding to ensure the firm's ability to finance future investments when the internal cash flow is low (Kim, Firm size is an important factor in determining the level of cash holding. Some of the literature argued that there is a negative relationship between firm size and cash holding, since small-sized firms are more exposed to irregular risks and borrowing restrictions, and then managers tend to maintain a higher level of cash holding to meet these restrictions and risks (Maheshwari et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On top of these observations, various studies [8][9][10][11][12] have been trying to explain the mechanisms behind the effects. For instance, Reference [8] showed that the momentum effect may be correlated to the past trading volume.…”
Section: Introductionmentioning
confidence: 99%